Development of Bacaria Learning Media (Cheerful Reading) in the Indonesian Language Subject for Grade 1 Students of MI Al Fatah Sumberjo - Yossa Adi Ferdana; Uci Ulfa Nur'afifah; Novia Rahma Rista Utami (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to develop digital learning media Bacaria (Ceria Reading) in Indonesian language subjects to improve the initial reading skills of first-grade students of MI Al-Fatah Sumberjo. The study used the Research and Development (R&D) method with the ADDIE model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of first-grade students of MI Al-Fatah Sumberjo. Data collection techniques were carried out through observation, interviews, validation questionnaires, and user response questionnaires. The product developed was an interactive learning application that contained materials on recognizing letters, vowels and consonants, reading syllables, reading simple words, and interactive activities equipped with images and audio pronunciation. The results showed that the Bacaria media obtained a high level of feasibility based on validation by media experts of 70% (valid), material experts of 93.75% (very valid), and language experts of 87.5% (very valid). In addition, teacher responses to the use of the media obtained a percentage of 94.4% with a very practical category, while student responses obtained a percentage of 98.8% with a very practical category. These results indicate that Bacaria media is feasible, practical, and can be used as an alternative learning medium to help improve students' beginning reading skills. Therefore, Bacaria has the potential to be an effective learning medium to support Indonesian language learning in early elementary school or Islamic elementary schools.